THE PROBLEMS OF THE MODERN SYSTEM OF NEW HOUSING - Литвин, О. Ю. (Scientific Progress & Innovations, 2015)
The individual problems of the modern system of new housing, their description in the world's economic literature are reviewed. The analysis of studies over this topic is implemented. The attention is focused on that part of the problems during the construction of new housing – high prices, corruption in the allocation of land, the implementation of developers various shadow schemes to artificially increase the cost of housing, lack of control from buyers over the targeted use of funds, system of customers, neglect of needs of certain categories of the population – can be resolved through the mechanism of housing cooperatives.